Genetic Modifiers of comatose Mutations in Drosophila: Insights Into Neuronal NSF (N-Ethylmaleimide-Sensitive Fusion Factor) Functions. - Sanyal, S.; Krishnan, K.S. (Journal of Neurogenetics, 2012)
By the middle of the 20th century, development of powerful genetic approaches had ensured that the fruit fly would remain a model organism of choice for genetic and developmental studies. But in the 1970s, a few pioneering groups turned their attention to the prospect of using the fly for neurophysiological experiments. They proposed that in a poikilothermic organism such as Drosophila, temperature-sensitive or "ts" mutations in proteins that controlled nerve function would translate to a "ts" paralytic phenotype. This was by no means an obvious or even a likely assumption. However, following directed screens these groups soon reported dramatic demonstrations of reversible ts paralysis in fly mutants. Resultantly, these "simple" experiments led to the isolation of a number of conditional mutations including shibire, paralytic, and comatose. All have since been cloned and have enabled deep mechanistic insights into synaptic transmission and nerve conduction. comatose (comt) mutations, for example, were found to map to missense changes in dNSF1, a neuron-specific fly homolog of mammalian NSF (N-ethylmaleimide-sensitive fusion factor). Studies on comt were also some of the first to discriminate between nuanced models of NSF function during presynaptic transmitter release that have since been borne out by experiments in multiple preparations. Here, the authors present an overview of NSF function as it is understood today, with an emphasis on contributions from Drosophila beginning with experiments carried out by Obaid Siddiqi in the Benzer laboratory. The authors also outline initial results from a genetic screen for phenotypic modifiers of comt that hold the promise of further elucidating NSF function at the synapse. Over the years, the neuromuscular system of Drosophila has served as a uniquely accessible model to unravel mechanisms underlying synaptic transmission. To this day, ts paralysis remains one of the most emphatic demonstrations of nerve function in an intact organism.